In vivo diagnosis of oral dysplasia and malignancy using optical coherence tomography: Preliminary studies in 50 patients - Wilder-Smith, Petra; Lee, Kenneth; Guo, Shuguang; Zhang, Jun; Osann, Kathryn; Chen, Zhongping; Messadi, Diana (Lasers in surgery and medicine, 2009)
Background In vivo, non‐invasive optical coherence tomography (OCT) permits high‐resolution imaging of tissue surfaces and subsurfaces, with the potential capability for detection and mapping of epithelial pathologies. Purpose To evaluate the clinical capability of non‐invasive in vivo OCT for diagnosing oral dysplasia and malignancy. Experimental Design In 50 patients with oral lesions, conventional clinical examination was followed by OCT imaging, then standard biopsy and histopathology. Two blinded, pre‐standardized investigators separately diagnosed each lesion based on (1) OCT and (2) histopathology. Results Intra‐ and inter‐observer agreement between diagnoses based on histopathology and imaging data was excellent, with κ values between 0.844 and 0.896. Sensitivity and specificity were also very good. Conclusions These data demonstrate the excellent capability of in vivo OCT for detecting and diagnosing oral premalignancy and malignancy in human subjects. Lasers Surg. Med. 41:353–357, 2009. © 2009 Wiley‐Liss, Inc.